Minimally Invasive Lateral Retroperitoneal Corpectomy for Treatment of Focal Thoracolumbar Kyphotic Deformity: Case Report and Review of the Literature - Petteys, Rory J.; Sandhu, Faheem A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Corpectomy is a frequently performed procedure for pathologies of the anterior spine including neoplasms, fractures, deformities, and osteomyelitis. Traditional approaches to the anterior thoracic spine and thoracolumbar junction are associated with significant perioperative pulmonary complications and morbidity. Posterior and posterolateral approaches minimize some of these complications but are somewhat limited in visualization of the anterior elements.Patient and Methods Here we report the case of a 49-year-old man with a remote thoracolumbar fracture and subsequent focal deformity treated with a minimally invasive lateral retroperitoneal corpectomy and open posterior arthrodesis.Conclusion Minimally invasive lateral corpectomy is a safe and effective option for deformity correction. We discuss the relative advantages and disadvantages of this approach and review the relevant literature.
Keywords: minimally invasive; trauma; spinal fusion